Analysis of Reading Ability Towards Reading Interest and Difficulty Factors in Elementary School Reading Teaching - Sarif Maulana; Muhammad Topikin; Muhamad Aditya Saputra (CV. Akademi Merdeka, 2025)
Reading is a basic language skill that is essential for effective written communication and cognitive development, especially in upper elementary school students. The reading process involves converting language sounds into written symbols, recognizing letters, and ultimately understanding the content of texts. Reading facilitates critical thinking and enhances language skills, especially in grades four through six, when students transition from learning to read to reading to learn. Reading interest significantly influences comprehension ability; however, many literacy programs focus too much on technical skills, neglecting student engagement. Population in study This is all over the leader educate especially in class four, five and six with totaling 720 participants This study investigated the reading ability of upper elementary school students, the impact of reading interest and cognitive strategies, and the adequacy of teaching methods while highlighting the need for comprehensive assessment to identify barriers to reading. The study This use method through samples and procedures with technique data analysis method dependence multivariate. School basis observed at SDN Kertawaninangun Cirebon Regency, using questionnaire for evaluate progress reading, interest, comprehension, and difficulties reading. Variable in study This use interest read, ability reading, and difficulties related reading with development reading and some aspect as well as indicator from every variables. Research results This show correlation ability student Woman more tend tall in interests and difficulties read compared to student male. This study makes a significant contribution to the field of education, especially in basic literacy, by comprehensively identifying the relationship between reading interest, reading ability, and reading difficulties. These findings enrich scientific understanding of internal and external factors that influence children's literacy development and provide an empirical basis for developing more effective, contextual, and sustainable reading intervention models at the elementary school level.